Parenting quality in drug-addicted mothers in a therapeutic mother–child community: the contribution of attachment and personality assessment - De Palo, Francesca; Capra, Nicoletta; Simonelli, Alessandra; Salcuni, Silvia; Di Riso, Daniela (Frontiers in Psychology, 2014)
Growing evidence shows that attachment is a key risk factor for the diagnosis and treatment of clinical diseases in Axis I, such as drug addiction. Recent literature regarding attachment, psychiatric pathology and drug addiction demonstrates that there is a clear prevalence of insecure attachment patterns in clinical and drug addicted subjects. Specifically, some authors emphasize that the anxious-insecure attachment pattern is prevalent among drug-addicted women with double diagnosis (Fonagy et al., 1996). The construct of attachment as a risk factor in clinical samples of drug-addicted mothers needs to be studied more in depth though. The present explorative study focused on the evaluation of parenting quality in a therapeutic mother-child community using attachment and personality assessment tools able to outline drug-addicted mothers’ profiles. This study involved 30 drug addicted mothers, inpatients of a therapeutic community. Attachment representations were assessed via the Adult Attachment Interview; personality diagnosis and symptomatic profiles were performed using the Structured Clinical Interview of the DSM-IV (SCID-II) and the Symptom Check List-90-R (SCL-90-R) respectively. Both instruments were administered during the first six months of residence in a therapeutic community. Results confirmed the prevalence of insecure attachment representations (90%), with a high presence of U patterns, prevalently scored for dangerous and/or not protective experiences in infanthood. Very high values (>5) were found for some experience scales (i.e. neglect and rejection scales). Data also showed very low values (1-3) in metacognitive monitoring, coherence of transcript and coherence of mind scales. Patients’ different profiles (U vs. E vs. Ds) were linked to SCID-II diagnosis, providing insightful indications both for treatment planning and intervention on parenting functions and for deciding if to start foster care or adoption proceedings for children.